P57 The IL28B gene SNP rs12979860 CC haplotype, predictor of response to treatment in chronic HCV infection, is associated to high numbers of CD56bright NK cells, low numbers of CD3-CD56-CD16+ NK cells and low HCV-specific IL-10 production. (6th September 2011) - Carey, I; Bruce, M; Mendes, A; Scalori, A; Joshi, D; Agarwal, K; Mieli-Vergani, G; Vergani, D
Abstract : Introduction: Single nucleotide polymorphisms (SNPs) rs12979860 and rs8099917 near the IL28B gene predict response to treatment in chronic hepatitis C (CH-C). Control of HCV infection is linked to strong immune responses. Little is known on the association between IL28B SNPs, innate and adaptive immune responses in relation to therapy outcome in CH-C. Aim: To evaluate the relationship between rs12979860 and rs8099917, pre-treatment frequency/phenotype of natural killer (NK) cells (innate immunity), HCV-specific immune responses (adaptive immunity), and Peg-IFN/ribavirin response. Method: Patients: 19 CH-C genotype 1 patients (13 males, median age 47 years) treated with Peg-IFN/ribavirin were divided in 3 groups: 10 responders (SVR), 5 non-responders (NR) and 4 relapsers (Rel). Methods: rs12979860 and rs8099917 were tested by direct sequencing. Baseline numbers of NK cells (CD3 − CD56 + ), their subsets CD56 dim /CD56 bright, CD3 - CD56 +/− CD16 +/−, and expression of NK cell activation/inhibition (NKG2D/NKG2A) markers were investigated by flowcytometry on peripheral blood mononuclear cells (PBMC). PBMC IFN-γ and IL-10 production after exposure to HCV-core, NS3, NS4, NS5 antigens was evaluated by intracellular cytokine staining. Results are presented as medians. Results: rs12979860 haplotype CC was present in 32% of patients (40% SVR and 50% Rel), CT in 63% (60% SVR, 50% Rel and 80%NR) and TT in 5% (20% NR); rs 8099917 haplotype TT was present in 68% (80% SVR, 75% Rel and 40% NR) and GT in 32% (20% SVR, 25% Rel and 60% NR). Baseline number of NK cells was similar in all groups, but that of CD56 bright cells was higher in SVR than Rel/NR (6.7% vs 3.3%, p=0.04). CD3 − CD56 − CD16 + cells were more frequent in NR and Rel than SVR (14.4% vs 10.1% and 7.7%, p=0.05). The proportion of CD56 dim cells NKG2D + was higher in SVR than Rel and NR (51.1% vs 37.3% and 25.2%, p=0.04). While number of HCV-specific IFN-γ producing cells was similar in all groups, IL-10 producing cells were higher in Rel and NR than SVR for HCV core (CD4 + /IL-10: 4.8% vs 3.5% vs 1.8%, p=0.05). Compared to patients with rs12979860 CT/TT haplotypes, those with CC haplotype had more CD56 bright cells (6.8% vs 3.5%, p=0.04), but fewer CD3 - CD56 − CD16 + NK cells (7.9% vs 14.2%, p=0.05) and HCV-core specific CD4 + /IL-10 + cells (4.5% vs 2.1%, p=0.05). There was no association between rs8099917 haplotypes, NK-cell number/phenotype and HCV-specific immune responses. Conclusion: High numbers of CD56 bright NK cells, low numbers of unconventional CD3 − CD56 − CD16 + NK cells, and low HCV-specific IL-10 production at baseline are associated with IL28B gene SNP rs12979860 CC haplotype and successful antiviral treatment of CH-C genotype 1.